(untitled) (Bangladesh Journal of Medical Science, 2021)
Background: Recently, there are many covid-19 like asymptomatic cases reported with negative RT-PCR presentation and this condition is classified as sub-clinical covid-19. It primarily affects the respiratory system and cause inflammation triggering blood clot formation leading to complications such as Stroke, Myocardial infarction. Very limited COVID-19 cases with Transient Ischemic Attack were observed. We report a case where the patient presented with Transient Ischemic Attack with underlying subclinical COVID-19. Case Presentation: A 70 years old male patient was admitted in medical intensive care unit with chief complaints of weakness and tingling sensation of left upper and lower limbs, slurred speech. The patient described that he had experienced with shortness of breath, cough, fever 10 days before hospitalization. Patient was primarily managed with IVmannitol, oral-ecosprin and intravenous fluids. Laboratory test was advised which showed elevated levels of inflammatory markers such as ESR, CRP, d-dimer, white blood cells, neutrophils, decreased lymphocytes. CT scan of chest revealed ground glass opacities and CT of brain suggested diffuse cerebral atrophy. But RT-PCR and Rapid antigen test was negative. Based on all these parameters patient was diagnosed with subclinical covid-19 with transient ischemic attack(TIA). Patient was treated with antibiotics, antiviral and supportive treatment was given for 8 days and then discharged from hospital after complete recovery. Conclusion: The patient presented with symptoms of transient ischemic attack and later diagnosed with subclinical covid-19 based on laboratory data and the symptoms he had experienced before 10 days of hospitalization. The patient was provided with appropriate treatment and discharged from hospital after complete recovery. Neurological complications and clotting disorders are increasingly observed with covid-19. Hence appropriate care should be taken for monitoring such conditions. Bangladesh Journal of Medical Science Vol.20(5) 2021 p.162-165